(untitled) - Heerkens, Gary (New York, 2006)
To make the leap from average to superior, you must develop the skills to manage each project like a small business. The Business-Savvy Project Manager thoroughly explains key concepts, principles, and tools for project managers to provide organizations with superior return-oninvestment and top performance. From portfolio management and strategic alignment to calculation of economic metrics and effective use of both financial and nonfinancial criteria in project proposals, it gives you the business savvy for top-level performance and certain career success
Keywords: Project management